Improving the effectiveness of the learning curriculum on children's railways through the development of environmental literacy and inclusive creative technologies - Dultsev I. A. (Pedagogy, Psychology, Society: from theory to practice, 2025)
The article describes an educational project aimed at increasing student engagement and consolidating educational material through the practical use of secondary resources. The author describes the experience of creating thematic dioramas as a means of visual representation of the studied sections of the program. Special emphasis is placed on the possibility of children with disabilities participating in the project, which made it possible to implement an inclusive approach to learning. The project was implemented as part of optional classes on the Sverdlovsk Children's Railway for five months. The participants used recycled materials such as cardboard boxes, old brushes, wires, book covers, etc. – as well as elements of modern technologies, including 3D printing. The work contributed to the development of creative, engineering and environmental thinking, communication skills and teamwork. The results showed the effectiveness of the method: children were actively involved in the learning process, showed independence and initiative, and also increased the level of understanding of the educational material. The project confirmed the potential of using accessible materials and inclusive practices to form sustainable knowledge and value orientations among students.
Keywords: инклюзивное образование; экологическая грамотность; дети с ОВЗ; творческие технологии; inclusive education; children with disabilities; creative technologies; environmental literacy; инженерное мышление; engineering thinking; secondary materials; dioramas; learning through practice; вторичные материалы; диорамы; обучение через практику